Comparative analysis of pancreatic cancer burden attributable to high BMI in adults aged 70 and older: analysis of the GBD data in the United States, Australia, and Germany (2012–2021) - Yang, Hanwen; Lei, Simeng; Fu, Yangkai; Zhang, Bo; Ji, Zhili (Frontiers in Oncology, 2025)
BackgroundPancreatic cancer (PC) is a highly lethal malignancy for which obesity is a major risk factor. With increasing global aging, the burden of PC is increasing in the elderly population.ObjectiveThe objective of this study was to analyze the association between high body mass index (BMI) and the burden of PC in people aged 70 years and older in the United States of America (USA), Australia, and Germany during 2012-2021.MethodsBMI-related PC mortality and disability-adjusted life years (DALYs) were extracted from the global burden of disease (GBD) 2021 database for people aged 70 years and older. Trends in the burden of disease were assessed using age-standardized rate (ASR), estimated annual percentage change (EAPC), and joinpoint regression analyses, and differences between the three countries were compared.ResultsFrom 2012 to 2021, BMI-related PC mortality and DALYs increased in all three countries, with the steepest rise in the USA (ASR from 3.12 to 3.65), followed by Australia (ASR from 2.05 to 2.65), and a relatively stable trend in Germany (ASR from 1.81 to 2.26). The increase was most pronounced in adults aged 70 years and older, with average annual growth rates of 3.05% in Australia, 0.55% in Germany (after 2019), and 1.71% in the USA. BMI-related PC mortality patterns varied by country: males had higher rates than females in the USA, while Germany showed the opposite trend. In Australia, men aged 70–74 had higher BMI-related PC mortality than women, but women had higher rates in all other age groups. All three countries exhibited rising BMI-related PC rates with age, though peak incidence occurred at different ages.ConclusionHigh BMI significantly increases PC burden in adults aged 70 years and older in the USA, Australia, and Germany. Countries should tailor obesity prevention and health management strategies to their specific contexts to address the health challenges of an aging society.